CD44 enhances tumor formation and lung metastasis in experimental osteosarcoma and is an additional predictor for poor patient outcome. (18th March 2013) - Gvozdenovic, Ana; Arlt, Matthias JE; Campanile, Carmen; Brennecke, Patrick; Husmann, Knut; Li, Yufei; Born, Walter; Muff, Roman; Fuchs, Bruno
Abstract Formation of metastases in the lungs is the major cause of death in patients suffering from osteosarcoma (OS). Metastases at presentation and poor response to preoperative chemotherapy are strong predictors for poor patient outcome. The elucidation of molecular markers that promote metastasis formation and/or chemoresistance is therefore of importance. CD44 is a plasma membrane glycoprotein that binds to the extracellular matrix component hyaluronan (HA) and has been shown to be involved in metastasis formation in a variety of other tumors. Here we investigated the role of CD44 expression on OS tumor formation and metastasis. High CD44 expression, evaluated with a tissue microarray including samples from 53 OS patients and stained with a pan‐CD44 antibody (Hermes3), showed a tendency (p < 0.08) to shortened overall survival. However, nonresponders and patients with lung metastases and high CD44 expression had significantly poorer prognosis than patients with low CD44 expression. Overexpression of the standard CD44 isoform (CD44s) and its HA‐binding defective mutant R41A in osteoblastic SaOS‐2 cells resulted in HA‐independent higher migration rates and increased chemoresistance, partially dependent on HA. In an orthotopic mouse model of OS, overexpression of CD44s in SaOS‐2 cells resulted in an HA‐dependent increased primary tumor formation and increased numbers of micrometastases and macrometastases in the lungs. In conclusion, although CD44 failed to be an independent predictor for patient outcome in this limited cohort of OS patients, increased CD44 expression was associated with even worse survival in patients with chemoresistance and with lung metastases. CD44‐associated chemoresistance was also observed in vitro, and increased formation of lung metastases was found in vivo in SCID mice. © 2013 American Society for Bone and Mineral Research.